2015
DOI: 10.1149/2.0221503jss
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ITO Electrode Modification Using CsF Solution on Performance of Organic Light-Emitting Diodes

Abstract: In this paper, the effects of indium tin oxide (ITO) surface modification on organic light-emitting diode performance are investigated. ITO electrodes were soaked in CsF solution of various concentrations and then subjected to ultraviolet (UV)-ozone treatment. The standard device structure is ITO/α-naphthylphenylbiphenyl diamine (NPB) (40 nm)/tris (8-hydroxyquinoline) aluminum (Alq3) (60 nm)/LiF (1 nm)/Al (150 nm). Modifying the ITO surface with the optimal 10 wt% CsF solution significantly improved device per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Figure 15d illustrates that immersion of ITO substrates in the CsF solution promotes the formation of In—F bonds due to these fluorine atoms chemically bonded onto the ITO surface. [ 232 ] Research on chlorination of ITO has also been reported, such as indium trichloride evaporation, Cl 2 ‐plasma etching, and chloroform treatment. [ 233 , 234 , 235 ] To reveal the detailed process of halogenation, Huang et al.…”
Section: The Contacts Of Mhp To Tcomentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 15d illustrates that immersion of ITO substrates in the CsF solution promotes the formation of In—F bonds due to these fluorine atoms chemically bonded onto the ITO surface. [ 232 ] Research on chlorination of ITO has also been reported, such as indium trichloride evaporation, Cl 2 ‐plasma etching, and chloroform treatment. [ 233 , 234 , 235 ] To reveal the detailed process of halogenation, Huang et al.…”
Section: The Contacts Of Mhp To Tcomentioning
confidence: 99%
“…Figure 15d illustrates that immersion of ITO substrates in the CsF solution promotes the formation of In-F bonds due to these fluorine atoms chemically bonded onto the ITO surface. [232] Research on chlorination of ITO has also been reported, such as indium trichloride evaporation, Cl 2 -plasma etching, and chloroform treatment. [233][234][235] To reveal the detailed process of halogenation, Huang et al studied the interaction of F and Cl on the ITO surface via density functional theory calculations and proved that the dramatic increase of the work function was derived from the strong surface dipole rather than the change of the electrochemical potential of ITO.…”
Section: Chemical Engineering For Tco Substratesmentioning
confidence: 99%
“…Common methods to decrease the energy barrier between the ITO and HTL are surface treatment and inserting a p-type buffer layer. Many modified methods, such as air or O 2 -plasma, 7 UV-ozone, 8 and fluoride solution 9 have been reported. These methods improve the ITO morphology and increase the ITO work function.…”
mentioning
confidence: 99%